Real-time measurement of ICD lead motion during stereotactic body radiotherapy of ventricular tachycardia - Knybel, Lukas; Cvek, Jakub; Neuwirth, Radek; Jiravsky, Otakar; Hecko, Jan; Penhaker, Marek; Sramko, Marek; Kautzner, Josef (Reports of practical oncology and radiotherapy, 2021)
BACKGROUND: Here we aimed to evaluate the respiratory and cardiac-induced motion of a ICD lead used as surrogate in the heart during stereotactic body radiotherapy (SBRT) of ventricular tachycardia (VT). Data provides insight regarding motion and motion variations during treatment. MATERIALS AND METHODS: We analyzed the log files of surrogate motion during SBRT of ventricular tachycardia performed in 20 patients. Evaluated parameters included the ICD lead motion amplitudes; intrafraction amplitude variability; correlation error between the ICD lead and external markers; and margin expansion in the superior-inferior (SI), latero-lateral (LL), and anterior-posterior (AP) directions to cover 90% or 95% of all amplitudes. RESULTS: In the SI, LL, and AP directions, respectively, the mean motion amplitudes were 5.0 ± 2.6, 3.4. ± 1.9, and 3.1 ± 1.6 mm. The mean intrafraction amplitude variability was 2.6 ± 0.9, 1.9 ± 1.3, and 1.6 ± 0.8 mm in the SI, LL, and AP directions, respectively. The margins required to cover 95% of ICD lead motion amplitudes were 9.5, 6.7, and 5.5 mm in the SI, LL, and AP directions, respectively. The mean correlation error was 2.2 ± 0.9 mm. CONCLUSIONS: Data from online tracking indicated motion irregularities and correlation errors, necessitating an increased CTV-PTV margin of 3 mm. In 35% of cases, the motion variability exceeded 3 mm in one or more directions. We recommend verifying the correlation between CTV and surrogate individually for every patient, especially for targets with posterobasal localization where we observed the highest difference between the lead and CTV motion.
Keywords: stereotactic body radiotherapy; ventricular tachycardia